How to meet your self eaudiobook The workbook for self-discovery. - LePera, Nicole (HarperAudio, 2022)
Most people are stuck living life on autopilot. Are you ready to break free? At the root of all healing work is awakening consciousness, a process of shining light into the darkness of the unknown. In recent years, Dr. Nicole LePera has become the leading voice in psychological self-healing, helping millions of people around the world rise out of survival mode to consciously create authentic lives they love. In her first book, How to Do the Work, Dr. Nicole offered readers a revolutionary, holistic framework for self-healing. Now, in How to Meet Your Self, she shares a book designed to help every listener uncover their Authentic Self. By objectively and compassionately observing the physical, mental, and emotional patterns that fill our days and create our current selves, we can more clearly see what we do not wish to carry into the future. We all fall into conditioned habits and patterns—products of our past—that lead to cycles of pain, stuckness, and self-destruction. But as Dr. Nicole shares, we also have the innate ability to awaken to and change the behaviors and habits that no longer serve us, allowing us to step into the highest versions of ourselves. And as you work through this book and witness these default habits, from sleep to movement to eating, through emotional reactivity and core beliefs, you will never again have to ask: "but where do I start?" How to Meet Your Self is a revolutionary guide, a kind and encouraging companion, and a comprehensive masterwork of self-understanding that will radically transform your inner work and outer world. Supplemental enhancement PDF accompanies the audiobook.